PENGARUH CAREER ADAPTABILITY TERHADAP SUBJECTIVE CAREER SUCCESS DENGAN PERCEIVED ORGANIZATIONAL SUPPORT SEBAGAI VARIABEL MODERASI PADA GURU TAMAN KANAK-KANAK ANGGOTA IKATAN GURU RAUDHATUL ATHFAL KABUPATEN BANYUMAS - Mukhammad Ibnu Syifa; Ugung Dwi Ario Wibowo; Retno Dwiyanti; Imam Faisal Hamzah (PSYCHOPEDIA : Jurnal Psikologi Universitas Buana Perjuangan Karawang, 2026)
This study aimed to examine the effects of career adaptability and perceived organizational support on subjective career success, as well as to analyze the moderating role of perceived organizational support in the relationship between career adaptability and subjective career success among kindergarten teachers who are members of the Raudhatul Athfal Teachers Association (Ikatan Guru Raudhatul Athfal/IGRA) in Banyumas Regency. This study employed a quantitative explanatory research design. The sample consisted of 104 teachers selected through simple random sampling from a population of 568 teachers. Data were collected online using the Subjective Career Success Inventory (SCSI), Career Adapt-Abilities Scale (CAAS), and Survey of Perceived Organizational Support (SPOS), and were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS version 4. The results showed that: (1) career adaptability had a positive and significant effect on subjective career success (p < 0.001; f² = 0.971); (2) perceived organizational support had a positive and significant effect on subjective career success (p = 0.030; f² = 0.041); and (3) perceived organizational support did not significantly moderate the relationship between career adaptability and subjective career success (p = 0.221; f² = 0.016). This study concludes that subjective career success among kindergarten teachers who are members of IGRA in Banyumas Regency is primarily self-driven, being determined by individuals' internal psychological capacities rather than by external workplace conditions. The implications of this study highlight the importance of formulating policies and work programs within the IGRA organization that focus on strengthening teachers' internal psychological aspects, particularly the dimension of career adaptability, as well as the necessity for teachers to raise self-awareness in independently enhancing their career adaptability capacity. Penelitian ini bertujuan untuk mengetahui pengaruh career adaptability dan perceived organizational support terhadap subjective career success, serta menganalisis peran perceived organizational support sebagai variabel moderasi pada Guru Taman Kanak-kanak anggota Ikatan Guru Raudhatul Athfal (IGRA) Kabupaten Banyumas. Metode yang digunakan adalah kuantitatif eksplanasi. Sampel penelitian terdiri dari 104 guru yang dipilih menggunakan teknik simple random sampling dari total populasi 568 guru. Pengumpulan data dilakukan secara online melalui skala SCSI, CAAS, dan SPOS, kemudian dianalisis menggunakan PLS-SEM dengan perangkat lunak SmartPLS versi 4. Hasil penelitian menunjukkan bahwa: 1) Career adaptability berpengaruh positif dan signifikan terhadap subjective career success (P-value = 0.000; f2 = 0.971). 2) Perceived organizational support berpengaruh positif dan signifikan terhadap subjective career success (P-value = 0.030; f2 = 0.041). 3) Perceived organizational support tidak terbukti memoderasi pengaruh career adaptability terhadap subjective career success (P-value = 0.221; f2 = 0.016). Penelitian ini menyimpulkan bahwa subjective career success pada guru TK anggota IGRA Kabupaten Banyumas bersifat self-driven yang dikendalikan oleh kapasitas psikologis internal individu, bukan hasil pengkondisian lingkungan kerja eksternal.  Implikasi penelitian ini menekankan pentingnya perumusan kebijakan dan program kerja organisasi IGRA yang berfokus pada penguatan aspek psikologis internal guru, khususnya dimensi career adaptability, serta pentingnya kesadaran guru untuk meningkatkan kapasitas adaptabilitas kariernya secara mandiri.